Identification of Land Use Changes Due to Changes in Coastlines in the Amurang Coastal Area, South Minahasa Regency - Simatupang, David; Rondonuwu, Dwight Mooddy; Warouw, Fela (Department of Urban and Regional Planning, Diponegoro University, 2025)
Indonesia's coastal areas are dynamic and vulnerable to physical, economic, and socio-cultural changes. This study aims to analyze land use change due to shoreline change in the coastal area of Amurang, South Minahasa Regency, 2005-2022. The main data used included Landsat 7 ETM+, Landsat 8 OLI/TIRS, and Landsat 9 OLI-2/TIRS-2 images, which were processed using GIS-based spatial analysis methods. Shoreline analysis was conducted using the Digital Shoreline Analysis System (DSAS) technique to measure changes in accretion and abrasion. The results showed significant changes in land use. In Kawangkoan Bawah Village, the water body turned into 9.23 hectares of green open space and 11.32 hectares of built-up area, in line with shoreline accretion with an average transect value of 68.11 meters. In contrast, in Lopana Village, green open space turned into 12.24 hectares of water body, corresponding to a dominant abrasion of -126.99 meters. An anomaly occurred in Kawangkoan Bawah Village, where built-up land turned into a water body of 2.36 hectares even though the shoreline in the area tends to experience accretion, which is due to the location of the land change not being directly in the area of shoreline change. This research confirms the importance of utilizing spatial analysis to understand the dynamics of coastal areas and the importance of adaptive spatial planning to manage the impacts of shoreline change.